Midterm results of “treat and repair” for adults with non-restrictive ventricular septal defect and severe pulmonary hypertension - Hu, Zhenlei; Xie, Bo; Zhai, Xinming; Liu, Jidong; Gu, Jianmin; Wang, Xudong; Zheng, Hui; Xue, Song (Journal of Thoracic Disease, 2015)
Background: A non-restrictive ventricular septal defect (VSD) can cause intracardiac left to right shunt, which leads to increased pulmonary vascular resistance (PVR) and pulmonary hypertension causes bidirectional or even right-left shunt, namely the Eisenmenger’s syndrome. For patients with non-restrictive VSD with severe pulmonary hypertension at stage of near or to be Eisenmenger’s syndrome, traditional VSD repair carries high mortality and poor prognosis. Recently, targeted drug therapy was used to decrease pulmonary circulation resistance in these patients before they receive defect repair surgery, namely “treat and repair” strategy, however, there is few reports about the midterm result of this strategy in adults with non-restrictive VSD with severe pulmonary hypertension at stage of near or to be Eisenmenger’s syndrome. Methods: In this study, we used this strategy to treat 41 adult VSD patients who received bosentan as the targeted therapy to decrease their PVR before and after repair surgery. Results: A total of 39 patients were followed up for an average of 37 months. None of the patients died during follow-up. Among them, 36 cases continued targeted drug therapy, whose mean pulmonary artery pressure (mPAP) was significantly reduced, including 31 cases with mPAP